Women detainees in Bacolod City their perceptions and concerns regarding the right to be free from sexual harassment. - Golez, Kriska Gowezi Marie M.
This study intended to identify the perceptions and concerns of women detainees in Bacolod City and what influences such perceptions. It also sought to find out how the specific concerns were being addressed at present and what the women detainees recommended in improving the existing efforts. As a descriptive research, it made use of in-depth interviews. This research was conducted on the women detainees in the Bacolod City Jail, Negros Occidental with 25 percent of the total population regarded as respondents. The sampling design of this research was a convenience purposive sampling. In addition to that, ethical considerations were observed., Different themes came about as the concepts of human rights (human rights as an institution, as the rights of persons, as the equality of individuals), sexual harassment, and the right to be free from sexual harassment were introduced. It was found out that all of the respondents were aware of the topic presented to them. They attributed their perceptions to different sources of information which have helped in shaping their understanding of their right against sexual harassment. The different sources include the television, radio, reading materials, school, family, peers, personal experience and the information from the Human Rights symposium that was conducted on a date prior to the conduct of this study. From their perceptions, various concerns originated. Since majority of the respondents were mothers, fear their families' safety was main concern. Others are bothered by a feeling of helplessness and inferiority as women. Sexual harassment, for the women detainees, is an issue that is worth being given attention to, especially by the government. While the Women's Desk, Barangay, and Jail are considered to be responsible with the existing institutional efforts, the respondents also suggested that laws be improved, women be included in the budget, more recreation and livelihood projects be put up, information be disseminated, and the family be made more aware. The results of this study showed that different sources of information shaped the various perceptions of women detainees in Bacolod City. These perceptions brought about specific concerns which, in turn generated institutional efforts. The existing efforts enabled the women to come up with the recommendations on how to better improve the protection of their rights. this research has shown that although some of the respondents may not be well- versed with the concepts, they still have, in their own understanding, perceptions about the nature of the concepts that were introduced to them. From there they were able to express their apprehensions regarding their right to be free from sexual harassment and, consequently, they were also able to come up with suggestions on how they would feel more secure in the society.